Management of Gridhrasi Through Panchakarma w.s.r to Sciatica - Vishalavva.N.Iranagoudra; Jairaj.P.Basarigidad; Rohini R.Patil (AYUSHDHARA, 2024)
Among the Vatavyadhi brought on by vitiated Vata and Kaphanubandha vata is Gridhrasi. The symptoms of Gridhrasi can be correlated with the symptoms of sciatica. Sciatica is one of the most common disorders, affecting 10% to 40% of the population. Sciatica affects people of all ages, but it particularly affects older folks in their fourth decade of life. Sciatica is a condition in which pain or discomfort radiates down one or both legs, starting in the lower back and ending at the sciatica nerve. The degree of sciatica pain can sometimes make it difficult for a person to go about their everyday activities. It has traits with the traditional Ayurvedic remedies. In Gridhrasi, pain corresponds to the following locations: Jaanu (knee), Jangha (calf), Paada (foot), Prusta (back), Sphik purva Kati (hip), and Uru (thigh), internal pharmaceuticals. Materials and Methods: A 25-year-old patient complained of lower back pain that was radiating to both of his lower limbs, Shanoushadhi and Panchakarma procedure were recommended. Result: The patient’s symptoms considerably subsided, and he was able to carry out his regular tasks without difficulty. Discussion: Together with internal medications, Sarvanga Parisheka, Churna Basti, Kati Basti, Sarvanga Abhyanga, Sthanika Patra Pottali Swedana, Sarvanga Bhaspha Swedana, Stha Lepa, and Yogabasti (Anuvasana Basti with Sahacharadi Taila, Erandamoola Niruha Basti) effectively managed the disease.